The Effect of C680T GPR43 Gene Variations to Its Interaction with Short Chain Fatty Acid (SCFA) In Type 2 Diabetes Mellitus - Rizky Amalia; Karyono Mintaroem; Loeki Enggar Fitri; Nashi Widodo; Hidayat Sujuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Diabetes is a disorder in the metabolism of carbohydrates, lipids and proteins with various causes. From the previous research, GPR43 is a potent clinical target for the treatment of type 2 diabetes. It can be activated by Short Chain Fatty Acid (SCFA) which is an organic fatty acid produced through fermentation of dietary fiber by bacteria in the distal intestine. The aim of this study was to analyze the effect of C680T GPR43 Gene Variations to Its Interaction with Short Chain Fatty Acid (SCFA) in silico. The study used 8 sequences of GPR43: ID AF024690, AC002511, EU432114, BC095535, BC096198, BC096199, BC096200, BC096201 and data of ligand (SCFA): acetic acid (CID 176), Butyric acid (CID 264) and Propionic acid (CID 1032). GPR43 was modelled using I-TASSER, Sequence and structural alignments were conducted using Bioedit and Superpose V.10, respectively. The Docking process was done using PyRx and molecular interaction was analyzed using Discovery Studio 2016. The Result showed that three types of SCFA bind to GPR43 variants T and GPR43 variant M obtained a similar pattern. The binding affinity from the largest to the smallest is butyric acid > propionic acid > acetic acid. GPR43 variant T has greater affinity to the SCFA than the GPR43 variant M. There is no differences of preference between GPR43 variant T and GPR43 variant M to bind SCFA.